Pheno- and genotypic characterization of Pasteurella multocida isolated from cats, dogs and rabbits from Brazil. (April 2016) - Ferreira, Thais Sebastiana Porfida; Moreno, Luisa Zanolli; Felizardo, Maria Roberta; de Gobbi, Débora Dirani Sena; Filsner, Pedro Henrique de Lima Nogueira; de Moura Gomes, Vasco Tulio; Moreno, Marina; Moreno, Andrea Micke
Highlights: Pasteurella multocida is present in Brazilian cats, dogs and rabbits. Isolated strains carry several genes codifying virulence factors. Strains from rabbits are discriminated from cats and dogs using PFGE. Sulfonamides and cotrimoxazole presented the highest resistance rates. Abstract: Pasteurella multocida is the causative agent of many diseases of economic importance in veterinary medicine and is characterized by high zoonotic potential. Pet animals can be infected and play a major role as carriers. This study aimed to characterize the genetic diversity of P . multocida isolated from dogs, cats and rabbits, and to evaluate their antimicrobial susceptibility profiles. A total of 620 animals were studied; 51 were positive for P. multocida and 92 strains were isolated. 60.9% of the strains belonged to the capsular type A, while the remaining were classified as non-typeable. The hgbA, ptfA, sodC, tadD and hsf2 genes were more frequent among the rabbit strains. Sulfonamides and cotrimoxazole presented the highest resistance rate, followed by erythromycin. PFGE clustered strains according to host species. Our results indicate that P. multocida from companion animals carry several virulence factors and are resistant to antimicrobials commonly used in human and veterinary medicine.